Wilayah Cakupan Pelayanan Pembeli di Pasar Bandar Buat Kecamatan Lubuk Kilangan Kota Padang - Nurul Qamilah; Agel Vidian Krama (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2018)
This study aims to obtain a description of the coverage area of visitor services Bandar Bandar Buat Kecamatan Lubuk Kilangan Kota Padang and how much influence of pull factors such as: accessibility, and distance, quality, price, completeness and type of goods. The type of this research is descriptive research by combining qualitative and quantitative approach, while approach taken in sampling is by accidental technique. The result of the research shows that: (1) The area of service coverage of visitors, especially buyers at Bandar Buat Market is spread in eleven urban villages, with seven sub-districts of Lubuk Kilangan, Tarantang, Beringin, Indarung, Padang Besi, Koto Lalang, Bandar Buat Village, Village of Batu Gadang and four other villages of the two districts different that Piai Tangah village, Village of Limau Manis, Binuang Kampung Dalam village contained in District Pauh, and village in the district Kuranji,. Factors influencing buyers to come shopping to Bandar Buat Market are 17% Accessibility by percentage, Goods type with percentage of 18%, Quality of Goods with percentage of 23%, Completed Goods with percentage of 22%, and Goods Price by percentage of 20%, the pull factor that became the main choice of visitors is the factor of quality of goods with a percentage of 23%. The conclusion is that there is an outline as the coverage area of Bandar Buat Market Services and there are several factors that influence the level of community shopping at Bandar Buat Market such as accessibility and distance, type of goods, completeness of goods, quality of goods and prices Keywords: Market, pull factor, the coverage area